Analisis Tingkat Ketimpangan Pendapatan dan Pengembangan Sektor Unggulan di Provinsi Daerah Istimewa Yogyakarta Tahun 2008-2020 - Elza Amriani; Fitrie Arianti (Universitas Diponegoro, 2022)
The economic growth of DI Yogyakarta Province tends to increase from 2008 to 2020. Meanwhile, there are still many districts or cities that are still coming in below average of DI Yogyakarta Province’s economic growth. Differences in economic growth show income inequality. Income inequality between regions can lead to development problems and economic instability. This study aims to analyze the magnitude of income inequality between regions and classify the leading regions in DI Yogyakarta Province, as well as to prove the Kuznets Hypothesis. The analytical methods used are Williamson index analysis and Location Quotient (LQ). The results showed that there are still many areas in DI Yogyakarta Province that are classified as relatively underdeveloped areas (quadrant IV). The income disparity between regions in Central Java Province in 2008-2020 is high (>0.5).